Identification of the SWEET gene family and functional characterization of PsSWEET1a and PsSWEET17b in the regulation of sugar accumulation in ‘Fengtang’ plum (Prunus salicina Lindl.) - Shan Liu; Xiaoshuang Nie; Hong Chen; Xinjie Shen (BMC Plant Biology)
Abstract Background ‘Fengtang’ plum is a cultivar known for its significant sugar accumulation. Although various studies have been conducted on sugar metabolism, the specific molecular mechanisms underlying the high sugar accumulation in ‘Fengtang’ plum remain largely unexplored. Here, we present the role of the Sugars Will Eventually be Exported Transporters (SWEETs) family in regulating sugar accumulation in ‘Fengtang’ plum fruits. Results In this study, 18 PsSWEET genes were identified based on homology with Arabidopsis genes and the Pfam database (ID: PF03083). Alignment of multiple sequences revealed that the seven alpha-helical transmembrane regions (7-TMs) are largely conserved in the PsSWEET family. Phylogenetic analysis demonstrated that the 18 SWEET family members could be categorized into four clades. Nine predicted motifs were identified within the PsSWEET genes of plum. The PsSWEET genes were unevenly distributed across five chromosomes, and synteny analysis revealed three pairs of fragmented duplication events. PsSWEET1a and PsSWEET17b are pivotal in ‘Fengtang’ plum fruit development. Subcellular localization analyses indicated that PsSWEET1a is localized to the nucleus and cytoplasm, while PsSWEET17b is associated with the vacuolar membrane. Gene function was further validated through transient silencing and overexpression of the PsSWEET1a and PsSWEET17b genes in plum fruits, which significantly impacted their soluble sugar content. Heterologous expression of PsSWEET1a and PsSWEET17b in tomato resulted in an increase in soluble sugar content due to the modulation of sugar accumulation-related genes and enzyme activities. Conclusion The genes PsSWEET1a and PsSWEET17b, which regulate the content of soluble sugar in plum fruit, were successfully identified. This study provides a comprehensive insight into the SWEET gene family of plum, offering novel perspectives on the regulation of sugar accumulation in fruit and laying a critical foundation for further enhancement of plum fruit quality.